METODE IJTIHAD DALAM KONSTRUKSI HUKUM TAHKIM INDONESIA - Nurul Khikmah; Karimatul Khasanah (Wahana Islamika Jurnal Studi Keislaman, 2022)
This paper provides input on where Tahkim or arbitration which is a form of dispute resolution outside the court and aims to reconcile the conflicting parties has existed and has long been practiced in the customs and culture of the Indonesian nation. However, with the increasing need for a peace model to resolve conflicts amid the rapid development of sharia business in Indonesia today, it is necessary to formulate a sharia tahkim model that accommodates local values. The fiqh rules clearly state that al hukmuyadurruma’aillatihi wujudan waadaman, that the law is enforced according to ilat whether it exists or does not exist, as well as the taghayyural-ahkam bitaghayural amkinat waal-azman rule that the law changes according to changes in place and time. The type of this research is juridical philosophical with maslahah approach. The data sources used are secondary and consist of three legal materials: primary, secondary, and tertiary. The type of this research is juridical philosophical with maslahah approach. The data sources used are secondary data sources consisting of three legal materials, namely primary, secondary and tertiary. The analysis was carried out using a descriptive inductive technique. The results of this study are that several ijtihad methods such as istihsan, maslahah mursalah, and especially the technique of establishing law with 'urf can be used to realize Indonesian Tahkim fiqh. The selection of these three methods, especially the 'urf which is based on benefit and istihsan is very suitable for conditions in Indonesia, considering that a culture of peace rooted in adat is still very strong.